Cone-Beam Computed Tomography in Orthodontics - Ahmad Abdelkarim (MDPI AG, 2019)
Unlike patients receiving implants or endodontic treatment, most orthodontic patients are children who are particularly sensitive to ionizing radiation. Cone-beam computed tomography (CBCT) carries risks and benefits in orthodontics. The principal risks and limitations include ionizing radiation, the presence of artifacts, higher cost, limited accessibility, and the need for additional training. However, this imaging modality has several recognized indications in orthodontics, such as the assessment of impacted and ectopic teeth, assessment of pharyngeal airway, assessment of mini-implant sites, evaluation of craniofacial abnormalities, evaluation of sinus anatomy or pathology, evaluation of root resorption, evaluation of the cortical bone plate, and orthognathic surgery planning and evaluation. CBCT is particularly justified when it brings a benefit to the patient or changes the outcome of the treatment when compared with conventional imaging techniques. Therefore, CBCT should be considered for clinical orthodontics for selected patients. Prescription of CBCT requires judicious and sound clinical judgment. The central question of this narrative review article is: when does CBCT add value to the practice of orthodontics? To answer this question, this article presents discussion on radiation dosage of CBCT and other imaging techniques used in orthodontics, limitations of CBCT in orthodontics, justifying the use of CBCT in orthodontics, and the benefits and evidence-based indications of CBCT in orthodontics. This review summarizes the central themes and topics in the literature regarding CBCT in orthodontics and presents ten orthodontic cases in which CBCT proved to be valuable.